2019
DOI: 10.1016/j.jad.2019.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Racing thoughts revisited: A key dimension of activation in bipolar disorder

Abstract: Background: Racing and crowded thoughts are frequently reported respectively in manic and mixed episodes of bipolar disorder (BD). However, questionnaires assessing this symptom are lacking. Here we aimed to investigate racing thoughts across different mood episodes of BD through a self-report questionnaire that we developed, the 34-item Racing and Crowded Thoughts Questionnaire (RCTQ). In addition to assessing its factor structure and validity, we were interested in the RCTQ's ability to discriminate mixed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 50 publications
(101 reference statements)
3
27
0
Order By: Relevance
“…Concerning the question of anxiety, our own studies have confirmed the view developed in the 2010 review [13] that there was a link between racing thoughts and anxiety both in the general population [20] and in mood disorders patients [19,24]. This link could rely on a common dimension of hyperarousal in anxiety states and in hypomanic or mixed bipolar states.…”
Section: Racing/crowded Thoughts and Other Illnessessupporting
confidence: 78%
See 2 more Smart Citations
“…Concerning the question of anxiety, our own studies have confirmed the view developed in the 2010 review [13] that there was a link between racing thoughts and anxiety both in the general population [20] and in mood disorders patients [19,24]. This link could rely on a common dimension of hyperarousal in anxiety states and in hypomanic or mixed bipolar states.…”
Section: Racing/crowded Thoughts and Other Illnessessupporting
confidence: 78%
“…Our recent studies confirmed the independence of the concept of racing/crowded thought and the concept of rumination by showing no relationship between the RCTQ score and the two subscales scores of the Ruminative Response Scale State version [60] neither in a general population sample [20] nor in a clinical sample [24]. Besides, a French study [61] showed that the level of depression in subjects initially admitted as emergencies for acute anxiety depressive disorders and/or suicide attempts was correlated with increased 'flow of thoughts', but not number of thoughts; these two dimensions were elegantly assessed by filling a drawing of an aquarium to reflect the number of thoughts (by drawing fish) and cognitive turmoil (by drawing wavy lines).…”
Section: Racing/crowded Thoughts and Depressive Ruminationmentioning
confidence: 51%
See 1 more Smart Citation
“…This makes the process-oriented VFT results all the more useful, as they provide a quantification of this clinical symptom, and improve the phenomenological models and scales aimed at evidencing enhanced spontaneous flexibility potentially involved in racing thoughts 14 . Importantly, clustering and switching abnormalities differentiated patients with manic symptoms, including the mixed depression group with few subthreshold – overlapping or not – hypomanic symptoms, from typical depression, suggesting that very few activation symptoms concurrent with depression might give rise to speech and thought abnormalities similar to those found in mania 25,37 .…”
Section: Discussionmentioning
confidence: 90%
“…In our study, instead of applying the DSM-5 criteria [ 9 ], we used a data-driven approach based on Miller et al [ 11 ] and Suppes et al [ 28 ] to determine whether patients were in a mixed episode or not. This approach has been favored in a number of recent studies which argue for the use of a less-restrictive diagnostic algorithm for the diagnosis of mixed states, including overlapping symptoms (distractibility, irritability, and psychomotor agitation) [ 7 , 11 , 45 , 47 ]. While the algorithms we used were less restrictive than the ones proposed by the DSM-5, there is an ongoing debate whether even less restrictive approaches focusing on specific features should be favored [ 7 ].…”
Section: Discussionmentioning
confidence: 99%